STRATEGI PENINGKATAN PEMASARAN PERUSAHAAN MARMER MM GALERI DI SIDOARJO - Rizka Indah Ariyanti; Fadjar Budianto (JPM17: Jurnal Pengabdian Masyarakat, 2017)
Plan strategic in competitive marketing started by analyze of competitor.Company differ value and customer satisfaction by value that be given price product,promotion, and distribution (marketing mix) on his competitor. With high competitionin trading , so strategic in marketing denotes me of important thing on enhance ofselling. Basically stratergy on marketing are wholl planning, integrated, and merge inmarketing fuld, can give guidance about activity will be done to get reach target ofmarketing in company. So strategy of marketing is very important to be needed toenhance of selling in the company, marketing strategy. Consists of, price , strategy ofdistribution , Strategy of promotion and place four strategy above also we called bymarketing mix. By four element of marketing mix above must be implemented base onlevel market competition will by target of company, on focus price strategy ormarketing strategy analysis to enhance off selling in marble company, and anotherstrategy four element of marketing mix improperly will make marketing activity, willbe useless and spend of human resource which is issued.